Development of green tourism in Ukraine - Korets, K. A. (ТДАТУ, 2019)
The main objective of green tourism is to get closer to nature and protect the environment. The advantages of this type of vacation are accessibility, privacy and uniqueness.
Keywords: Green Tourism; tourism; ecotourism